Stability of the water levels regime on the lakes in Poland - Wrzesiński, Dariusz; Plewa, Katarzyna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
The paper presents the results of a study into the stability of water-level regimes in Polish lakes. Stability is defined as a degree of regularity with which a certain phase of the hydrological regime occurs (high and low water levels). The hydrological regime is described with the use of the following 6 variables – first, second and third maximum; first, second and third minimum. Stability of the hydrological regime is determined by the stability coefficient (WS). The analysis relies on data concerning average monthly values of water levels for 34 lakes located in Polish lake regions. There are characteristic spatial differences in the stability of maximum and minimum water levels which are usually caused by environmental factors and human activity. It was observed that the most stable dates were those of the 1st maximum and the 1st minimum. In the case of the lakes in the Pomeranian, Wielkopolsko-Kujawskie and Mazurian lake districts, the occurrence date of the 1st maximum is highly stable and stable, while the date of the 1st minimum is the most stable in the lakes of the Drawsko, Wielkopolsko-Kujawskie and Mazurian lake districts.
Keywords: water-level regime; stability coefficient; lakes